EFEKTIVITAS PEMBALUT EKSTRAK DAUN MIANA (COLEUS SCUTELLARIOIDES) TERHADAP PENYEMBUHAN LUKA PERINIUM PADA IBU POSTPARTUM - Utami, Fetty Satu Ryan; Rahayu, Sri; Supriyadi, Supriyadi (Media Penelitian dan Pengembangan Kesehatan, 2024)
Poor perineal wound care can cause infection and impact the wound-healing process. Miana leaves contain flavonoids that are antibacterial and anti-inflammatory and prevent infection. For this reason, researchers developed a sanitary napkin product with Miana leaf extract to accelerate the healing of perineal wounds in postpartum mothers. The study aimed to determine the effectiveness of Miana leaf extract dressings in accelerating the healing of perineal wounds in postpartum mothers. The research type was true experimental with a pretest post-test design and a control group design using a simple random sampling technique. The respondents were postpartum mothers with grade II perineal wounds divided into two groups of 20 samples. Provide miana leaf extract dressings and dry clean treatment 3 times a day for 7 days. Wound measurements using REEDA and Staphylococcus aureus bacteria in the laboratory. Bivariate analysis using Friedman and Wilcoxon. The average REEDA score pre-day 3, 5, and 7 in the intervention group was 12.10, 3.65, 0.95, and 0.15; in the control group, it was 13.20, 12.65, 10.95, and 9.35. The average pre and post-Staphylococcus aureus bacteria in the intervention group was 4.15, and 0.35 in the control group was 5.10 and 3.15. Miana leaf extract effectively reduced wound healing time (p=0.038) and the number of Staphylococcus aureus bacteria (p=0.006). Using Miana leaf extra dressing for 3 days effectively reduces the length of wound healing and the number of Staphylococcus aureus bacteria in postpartum mothers with grade II perinatal wounds.